Rachel's secret - Hoff, B. J., 1940- (Eugene, Or. : Harvest House Publishers, 2008)
Jeremiah Gant, a wounded Irish American riverboat captain, creates a stir when he bursts into the rural Amish setting of Riverhaven, but as he seeks out a safe place to recuperate, neither he nor Rachel Brenneman, a young widow, are prepared for a forbidden love that threatens to endanger a way of life for an entire community.
Keywords: Amish -- Fiction; Love stories; Christian fiction